ANALISIS FLANGE MESIN DARI PROSES PENGECORAN PASIR - Kelvin, Michael; Akbar Triatmojo, Kurnia; Musyaffa' Ma'shum, Yafi'; Arman, Rifqi; Ardiansyah Darmawan, Mohamad; Prasetyo Pangestu, Andika; Fadilah, Risky; Laila Sari, Shintya; Raharjo, Rudianto (Program Studi Teknik Mesin Fakultas Rekayasa Sistem Universitas Teknologi Sumbawa, 2024)
The Engine Flange is a crucial component in engines and engine systems, used to connect or mount the engine onto other structures or parts of vehicles. It serves as a strong and stable attachment point, allowing the engine to be securely and accurately positioned. The Engine Flange consists of two arms with matching holes to accommodate the propeller shaft. Engine Flanges can be produced through the metal casting process using sand molds (sand casting). The most commonly used material for making Engine Flanges is aluminum. Economically, sand casting is the most cost-effective method compared to others. There are many variables to consider in the metal casting process to obtain high-quality products with minimal defects. Therefore, process optimization is necessary to minimize defects that may occur during casting. Subsequently, metal casting simulations were performed using Altair Inspire Cast 2023 software to identify and compare the defects produced. The aim of this research is to compare actual casting results with simulations to identify defects in actual castings and simulation results. After the research, similar defects were found between the actual castings and simulation results, such as microporosity, porosity, shrinkage, mold erosion, and air entrapment. However, there were also other defects present in the actual castings, such as fins, sand inclusions, shrinkage, misruns, and swells.